A Preliminary Survey Report on the Working of the Research-cum-Action Projects - Planning Commission (Planning Commission, 1960)
"In letter No. F/25/l-23 /59-Pl dated the 1st February, 1960, the Ministry of Health, Government of India requested the Programme Evaluation Organisation to evaluate the working of the Research - cum -Action Projects in environmental sanitation. They agreed that the procedure for the evaluation Would he determined by the Programme Evaluation Organisation. At a meeting, presided over by the Chairman, PEB, with the officers of the Ministry of Health, it was decided that the P.E.O. would, with the help of an Administrator to bo appointed by the Ministry of Health, evaluate the work of the RCA Projects in anvironmuntal sanitation and, in particular, assess the validity of the preliminary findings of the RCA centres. As a result of some changes the initiation of the original plan of investigation was delayed. Moreover as the Administrator could not bo appointed early enough, it was considered advisable to carry out a preliminary survey of the working of RCA Projects in relation to the use position, the educational efforts and general organisation of the RCA Projects with the PEG staff only."
"Envlronmental Sanitation With Particular Emphasis On Rural Latrines"